Antimicrobial Activities and Painting Application of Pigmented-Producing Actinobacteria Isolated from Rhizospheric Soils of Mosses (Taxithelium nepalense (Schwägr.) Broth. and Barbula indica (Hook.) Spreng.) - Urtgam, Sittichai; Thananoppakun, Kanjana; Puengtang, Chaowalit; Sumpradit, Tawatchai; Thuankul, Bantita; Thurnkul, Naruemol (Bogor Agricultural University, Indonesia, 2024)
In the survey of biodiversity of actinobacteria associated with mosses (Taxithelium nepalense (Schwägr.) Broth. and Barbula indica (Hook.) Spreng.), certain strains of pigment producing actinobacteria were isolated and purified on SCA and incubated at 30°C for 1 week. Based on deep-shade color of actinobacterial pigments, 4 strains were collected and used for painting color preparation. To evaluate the antimicrobial activities, the crude extracts were prepared from 4 actinobacterial strains and tested with Escherichia coli PSRU-01 and Staphylococcus aureus PSRU-01. The results indicated that the crude extracts of C7, C13, C15 and D13 could not inhibit growth of E. coli PSRU-01, but S. aureus PSRU-01 was inhibited. Two fungal testers, including Colletotrichum sp. PSRU-01 and Fusarium sp. PSRU-01, were completely inhibited by the crude pigment extracts of C13, C15 and D13. Based on phylogenetic results, the actinobacterial strains were closely related to Streptomyces californicus (C7, 100% identity), Streptomyces bungoensis (C13, 99.8% similarity), Streptomyces humi (C15, 99.9% similarity), and Streptomyces rectiverticillatus (D13, 99.8% similarity). They also shared phenotypic characteristics with Streptomyces. The cultivated cells of actinobacteria on broken-milled rice were used for pigment extraction and followed by determination of the extracted pigments for mixing with acrylic color in the shade violet, green, orange and pink colors. Application of actinobacterial pigments in painting is the first report and it is an innovative utilization of actinobacterial pigments in non-scientific field in Thailand.